2010
DOI: 10.3354/dao02171
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ‘Candidatus Piscichlamydia salmonis’ in Arctic charr Salvelinus alpinus during a survey of charr production facilities in North America

Abstract: Arctic charr Salvelinus alpinus production facilities, nonproduction water sources and effluents in the United States and Canada were sampled to determine if chlamydiae associated with epitheliocystis were present in water and were associated with inclusions of epitheliocystis in gill tissue. Gills from 607 fish from 13 sites were processed for histopathologic examination and DNA extraction. Water was collected from 21 locations for DNA testing. Eighteen fish from one location had inclusions of epitheliocystis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 53 publications
1
30
1
6
Order By: Relevance
“…Epithelial hyperplasia, epithelial lifting along the lamellae, and lamellar fusion in the striped trumpeter were observed, although the filling of the interlamellar spaces was not as severe as that in previous reports. This differs from the nearly complete filling of the interlamellar spaces reported in both the largemouth bass (28) and the Arctic charr (15,27), which resulted in a severely compromised respiratory system. Striped trumpeter fish were recently reported to be affected by epitheliocystis (6).…”
Section: Simkania Negevensis Fr872582contrasting
confidence: 51%
See 2 more Smart Citations
“…Epithelial hyperplasia, epithelial lifting along the lamellae, and lamellar fusion in the striped trumpeter were observed, although the filling of the interlamellar spaces was not as severe as that in previous reports. This differs from the nearly complete filling of the interlamellar spaces reported in both the largemouth bass (28) and the Arctic charr (15,27), which resulted in a severely compromised respiratory system. Striped trumpeter fish were recently reported to be affected by epitheliocystis (6).…”
Section: Simkania Negevensis Fr872582contrasting
confidence: 51%
“…Epitheliocystis is now known to affect Ͼ80 different species of fish (7,10), and intriguingly, from all of these reports, it appears that the host responses considered to be severe or as having a hyperinfection are all from farmed fish (14)(15)(16)(27)(28)(29)(30)(31)(32). Molecular diagnostics confirmed that this CLO, from both cultured and wild sources, is a member of the order Chlamydiales, based on the Ͼ80% sequence similarity to other species in the order (18).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These results confirm a recent report that 'Ca. P. salmonis' is not restricted to seawater (Draghi et al 2010). No conclusions can be made at this stage regarding the possible contribution of freshwater infections of either 'Ca.…”
Section: Discussionmentioning
confidence: 96%
“…This agrees with previous reports for the molecular description of "Ca. Piscichlamydia salmonis" in Atlantic salmon (24,47) and Neochlamydia-like bacteria in Arctic charr (14).…”
Section: Discussionmentioning
confidence: 99%